Designing a typical model for producing a static and animated infographic for higher studies - Amany El Mor (International Journal of Advanced Humanities Research)
The present study aimed at designing a typical model for producing a static and animated infographic. In order to test the validity of this model, the study was applied on 14 male and female of higher students at faculty of education, Tanta University of the year 2019/2020. A list of skills concerning designing and producing the static and animated educational infographic besides making a card for evaluating the infographic model have been prepared. The results showed that the quality of the products and models students made according to the steps of the prepared model. That showed the importance of using this typical model when producing the static and animated educational infographic